2020
DOI: 10.1002/jmv.25897
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label use of tocilizumab in patients with SARS‐CoV‐2 infection

Abstract: The spread of the novel-Coronavirus infection worldwide represents a challenge for physicians. Particularly, no approved therapy has demonstrated to have an impact in treating patients who develop severe respiratory insufficiency so far. The use of humanized anti-human inteleukine-6 receptor antibody tocilizumab seems a promising strategy for these patients.Dear Editor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
2
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 6 publications
4
99
2
6
Order By: Relevance
“… 22 Our results may suggest that “critically ill” COVID-19 patients should be sub-divided into two sub-cohorts as patients who developed a requirement for advanced oxygen support later in their hospital course (progressive) had a distinct inflammatory biomarker profile than patients who required immediate intubation on hospital admission (severe). Multiple randomized control trials are examining tocilizumab in COVID-19 infection, 23 , 24 , 25 , 26 , 27 and preliminary results from recent phase III studies have been mixed. The COVACTA trial evaluating tocilizumab (F. Hoffmann-La Roche, press release: https://www.roche.com/investors/updates/inv-update-2020-07-29.htm ) and another trial centered on sarilumab (Sanofi-Aventis U.S., press release: https://www.sanofi.com/en/media-room/press-releases/2020/2020-07-02-22-30-00 ) did not meet primary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Our results may suggest that “critically ill” COVID-19 patients should be sub-divided into two sub-cohorts as patients who developed a requirement for advanced oxygen support later in their hospital course (progressive) had a distinct inflammatory biomarker profile than patients who required immediate intubation on hospital admission (severe). Multiple randomized control trials are examining tocilizumab in COVID-19 infection, 23 , 24 , 25 , 26 , 27 and preliminary results from recent phase III studies have been mixed. The COVACTA trial evaluating tocilizumab (F. Hoffmann-La Roche, press release: https://www.roche.com/investors/updates/inv-update-2020-07-29.htm ) and another trial centered on sarilumab (Sanofi-Aventis U.S., press release: https://www.sanofi.com/en/media-room/press-releases/2020/2020-07-02-22-30-00 ) did not meet primary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…56 Understanding the mechanisms underlying different prognosis in children is essential for designing targeted therapies for COVID-19. targeting the CRS and hyperinflammatory status of lung destruction via anti-IL-6R antibodies, [218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235][236][237] IL-1R antagonists, [238][239][240] JAK-STAT inhibitors, 241 or inhibition of entrance by anti CD147 antibodies 237 and destruction of the virus via protective antibody delivered with convalescent plasma 51,54,66,133,134,242 (Table 2). Eculizumab targets complement protein C5 preventing activation of complement terminal complex, which was used off label in patients with SARS-CoV-2 infection and severe pneumonia or ARDS and is now evaluated in an ongoing trail (SOLID-C19).…”
Section: Kids Versus Adults: Mechanisms Explaining the Clinical Difmentioning
confidence: 99%
“…Di Giambenedetto et al. highlighted the efficacy of tocilizumab in the treatment of COVID-19 without detected adverse events and suggested that tocilizumab may be an effective and safe treatment of COVID-19 patients with severe pneumonia [ 82 ].…”
Section: Diagnosis Treatment and Preventionmentioning
confidence: 99%